Peran Media Sosial sebagai Strategi Optimalisasi Pemasaran pada UMKM Perdana Semarang - Widiyanti Widiyanti; Ratna Tunjungsari; Agung Budiartono (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2026)
Marketing is the spearhead of any business. Optimal marketing will certainly create greater opportunities for a product to be better known to the public, increase product demand, create a positive brand image and corporate image, so that targeted sales can be achieved. Marketing is a source of income, so it is crucial to pay attention to how to optimize product marketing strategies. The dynamic era of modern life, where effectiveness and efficiency become a passion, can also be seen from the intense use of digital marketing. Digital marketing, in addition to being able to reach a wider market and supporting marketing cost efficiency, also creates unlimited marketing space and time. Furthermore, digital marketing is real-time, so business actors can directly monitor the interests and feedback from the target market. The research method used a qualitative method with a single case study research design. Using a non-probability sampling method with purposive sampling. Data collection was carried out through observation, in-depth interviews, and documentation. Data analysis included data reduction, data display, and conclusion drawing/verification. Data credibility was tested using triangulation and member checking.